Pengaruh Bauran Pemasaran Terhadap Kepuasan Dan Loyalitas Pelanggan Pada Klinik Kecantikan Felisa Skin Care Di Rengat Kabupaten Indragiri Hulu - akbar Surya Atmaja; Zulkarnain; Kasman Arifin (Jurnal Economica, 2020)
Effect of Marketing Mix on Customer Satisfaction and Loyalty in Felisa Skin Care Beauty Clinic in Rengat, Indragiri Hulu Regency.This study aims to see and know the direct and indirect effects of the Marketing Mix on Customer Satisfaction and Loyalty. The population in this study were all customers of the Beauty Clinic Felisa Skin Care Rengat Branch and Belilas Branch with a total of 496 people and determine the number of samples using the Slovin method to obtain 221 people. The results of this study found that the marketing mix affects Consumer Satisfaction and Marketing Mix influences customer Loyalty through Satisfaction.